Conditions for recovery from alcohol and drug abuse – comparisons between male and female clients of different social position. Issue 3 (1st September 2016) - Skogens, Lisa; von Greiff, Ninive
Abstract: This study adduces an interactive perspective on treatment and relates to research describing change as a process. It focuses on differences in how the importance of internal and social factors for the change process is described among male and female clients of different social position. The concept of recovery capital is used as analytic tool. Female and male clients were interviewed and asked to talk about factors they perceived as important for initiating and maintaining change. The use of a relatively large amount of interviews strengthen the possibilities of drawing generalized conclusions on differences between the groups, making comparisons possible while still keeping the qualitative meaning of the investigated factors. The most important finding in the study is that the implications of different factors during the change process seem to relate to gender stereotypes and that the client's social position (defined as marginalized or integrated) seems to be important for how gender stereotypes emerge. It is argued that gender stereotypes can serve both as a support and a hinder during recovery. This is discussed using the concept of recovery capital to illuminate qualitative differences regarding the importance of internal and social factors for the process of change for men and women of different social position.